The Importance of Enrichment in Wildlife Rehabilitation (Part Two) - Gulas–Wroblewski, Bonnie (Wildlife Rehabilitation Bulletin, 2008)
Environmental and behavioral enrichment has been assembled into five major categories: physical, nutritional, social, occupational, and sensory enrichment. Many of the enrichment strategies targeted at motivating species–specific behaviors and eliminating abnormal behaviors span multiple subsets of this system. For this reason, it is important to assess each category of enrichment when devising an enrichment device to accomplish the desired goal.